2020
DOI: 10.11648/j.ajche.20200803.11
|View full text |Cite
|
Sign up to set email alerts
|

Energy Saving Research on Multi-effect Evaporation Crystallization Process of Bittern Based on MVR and TVR Heat Pump Technology

Abstract: This work keeps an eye on the energy saving research on evaporation crystallization process of bittern. Based on the thermo sensitivity of solubility of various salts in bittern, the magnesium salts are purified. The conventional evaporation crystallization process used to separate the bittern demands high energy consumption and has low thermodynamic efficiency. Therefore, the multi-effect evaporation (MEE), thermal vapor recompression (TVR) heat pump and mechanical vapor recompression (MVR) heat pump technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…TVR is a technology for recovering waste heat as useful energy through mechanical compression [ 21 ]. Figure 3 provides a simplified diagram of the alternative process model using TVR.…”
Section: Methodsmentioning
confidence: 99%
“…TVR is a technology for recovering waste heat as useful energy through mechanical compression [ 21 ]. Figure 3 provides a simplified diagram of the alternative process model using TVR.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have demonstrated that multi-effect evaporation reduces energy consumption by enhancing the steam economy. This is achieved utilizing the secondary steam generated by the preceding effect as the heat source for the subsequent effect [6].…”
mentioning
confidence: 99%